Transmediación en la televisión peruana - Vásquez, Guillermo (Conexión, 2016)
Transmedia storytelling is gaining increasingly more presence in narrations thatpeople access through different media or platforms. In fact, this is not unawareto the Peruvian’s television contents in which the transmedia stories have startedappearing though with noticeable shyness and almost in proof-period, becausethe audience is still unfamiliar to the new tendency. In this article, an incipientreferent of transmedia in the public Peruvian television is examined. Theexposition is centered on the characteristics of the most recent manifestationsof the phenomenon.